Financial Liberalization & Economic Growth: Theoretical Overview - Elhag, Abubakr Eltigani (Journal of Humanities & Social Sciences, 2025)
This study examines the effects of financial liberalization on economic growth through a comprehensive review of theoretical and empirical literature. The research addresses the ambiguity surrounding these effects by employing a descriptive approach, analyzing historical and contemporary studies, and incorporating empirical evidence from developing countries. The findings indicate that financial liberalization generally has a positive impact on economic growth, particularly when prerequisites such as strong institutions, good governance, and macroeconomic stability are in place. However, some studies caution that improper implementation can lead to financial crises. The study highlights the benefits of gradual liberalization, enhanced competition in the banking sector, and the role of Islamic banking in adapting to global financial integration. Recommendations include investing in financial technology, improving workforce training, and strengthening regulatory frameworks to mitigate risks.
Keywords: Financial liberalization; Economic growth; GATS; Banking sector; Developing countries; Regulatory frameworks